Pengaruh obat kumur beralkohol terhadap laju aliran saliva dan pH saliva - Rawung, Feiby; Wuisan, Jane; Leman, Michael A. (Universitas Sam Ratulangi, 2017)
Abstract: Mouthwash is one of the accessible oral healthcare and practical for use by the community. Various commercial products contain more than one active ingredient; the most common one is alcohol with varied concentrations from 6% to 26%. Mouthwash with high concentration of alcohol can cause some effects to some users, like burning and dry sensation of the oral mucosa. Dry oral mucosa caused by reduced saliva production will be more susceptible to irritation. Reduced amount of saliva also causes lower oral pH which leads to increased growth of cariogenic bacteria. This study was aimed to investigate the influence of alcoholic mouthwash to salivary flow and salivary pH. This was a quasi-experiment study with before and after treatment groups. The population study was students of Dental Medical Education Program of Medical Faculty of University of Sam Ratulangi, Manado, batch 2012, with a total of 30 respondents obtained by using purposive sampling method. The T test showed that salivary flow rate before and after treatment had no significant difference (p >0.05) based on T test. Moreover, the Wilcoxon test showed that there was no significant difference of salivary pH between before and after treatment (p >0.05). Conclusion: There was no effect of rinsing with alcoholic mouthwash on salivary flow and salivary pH.Keywords: alcoholic mouthwash, salivary flow rate, salivary pHÂ Abstrak: Obat kumur merupakan salah satu produk perawatan kesehatan gigi dan mulut yang mudah diperoleh dan praktis digunakan sendiri oleh masyarakat. Berbagai produk komersial mengandung lebih dari satu bahan aktif; salah satunya yaitu alkohol dengan konsentrasi bervariasi dari 6% hingga 26,9%. Kandungan alkohol yang tinggi dapat menimbulkan efek bagi sebagian pengguna, seperti sensasi terbakar dan kering di area mukosa mulut disebabkan berkurangnya saliva yang memudahkan terjadinya iritasi. Berkurangnya saliva juga menyebabkan pH mulut rendah sehingga pertumbuhan bakteri kariogenik meningkat. Penelitian ini bertujuan untuk mengetahui adanya pengaruh obat kumur beralkohol terhadap laju aliran saliva dan pH saliva. Jenis penelitian ialah eksperimen semu dengan kelompok sebelum dan sesudah perlakuan. Populasi penelitian yaitu mahasiswa Angkatan Tahun 2012 Program Studi Pendidikan Dokter Gigi, Fakultas Kedokteran, Universitas Sam Ratulangi Manado yang berjumlah 30 responden, diperoleh dengan purposive sampling. Hasil uji T berpasangan mennunjukkan data laju aliran saliva sebelum dan sesudah perlakuan tidak memiliki perbedaan bermakna (p >0,05). Berdasarkan uji Wilcoxon, data pH saliva sebelum dan sesudah perlakuan tidak memiliki perbedaan bermakna (p >0,05). Simpulan: Tidak terdapat pengaruh berkumur dengan obat kumur beralkohol terhadap laju aliran saliva dan pH saliva.Kata kunci: obat kumur beralkohol, laju aliran saliva, pH saliva